Dynamic Modelling for Supply Chain Management Dealing with Front-end, Back-end and Integration Issues - Crespo Márquez, Adolfo; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2010)
An effective supply chain results in a clear competitive advantage for the production system as a whole, but supply chain management is a collaborative effort that requires the efforts of disparate groups of people and a wide range of expertise. Dynamic Modelling for Supply Chain Management discusses how to streamline complex supply chain management by making the most of the growing number of tools available. The reader is introduced to the basic foundations from which to develop intelligent management strategies, as the book characterises the process and framework of modern supply chain management. The author reviews supply chain management concepts and singles out important factors in the management of modern complex production systems. Particular attention is paid to modern simulation modelling tools that can be used to support supply chain planning and control. Coverage of the main problems related to supply chain management is organised into three different groups: front-end, back-end and integration issues. Traditionally, supply chain management focused on logistics but, in recent years, understanding and responding to customers’ needs have become much more critical. The book explores the operational and financial impacts of various potential problems, offering a compilation of practical models to help identify solutions. A useful reference on supply chain management, Dynamic Modelling for Supply Chain Management will benefit engineers and professionals working in a variety of areas, from supply chain management to product engineering. All the topics covered are illustrated with case studies drawn from several different sectors.
An Introduction to Dynamic Modelling for Supply Chains -- On the Definition of Dynamic Simulation -- Current Supply Chains Management Issues -- Models for SCM Simulation and Analysis -- Modelling Front-end Issues in SCM -- Understanding a Customer’s Decision to Buy -- Understanding Financial Implications of Strategy -- Understanding Hi-tech Business Growth -- Modelling a Hi-tech Business Growth -- Modelling Back-end Issues in SCM -- Back-end Issues Related to Supplier Management -- Modelling a Portfolio of Contracts with Suppliers -- Modelling Back-end Issues in Manufacturing -- Modelling Integration Issues in SCM -- Different Supply Chain Integration Models -- Modelling Financial Implications of Integration Strategies -- Exploring the Use of Manufacturing Control Techniques in Virtual SC -- Capacity Constraints Analysis for SCM -- Modelling Diversity Integration in the Organisation -- Dynamic Modelling Projects -- Presenting SCM Dynamic Simulation Projects -- Capturing the Learning of a Modelling Project.
Keywords: Engineering economics; Engineering economy; Production management; Computer-aided engineering; Engineering Economics, Organization, Logistics, Marketing; Operations Management; Computer-Aided Engineering (CAD, CAE) and Design